SIMDOM: A framework for SIMD instruction translation and offloading in heterogeneous mobile architectures - Shuja, Junaid; Gani, Abdullah; Ko, Kwangman; So, Kyoungyoung; Mustafa, Saad; Madani, Sajjad A.; Khan, Muhammad Khurram (Wiley, 2017)
Fog and mobile edge computing is a paradigm that augments resource-scarce mobile devices with resource-rich network servers to enable ubiquitous computing. Smartphone applications rely on code offloading techniques to leverage high-performance computing opportunities available on edge and cloud servers for compute-intensive applications. Mobile (ARM) and edge/cloud (x86) architectures are heterogeneous and necessitate dynamic binary translation for compiled code migration that increases the application execution time. The application execution time and energy consumption should be lesser on the edge/cloud server as compared with the local mobile execution for optimal offload. Multimedia-based applications contain a large set of single instruction multiple data (SIMD) instructions that are compute and resource intensive. However, dynamic binary translation techniques of SIMD instructions lose the parallelism and optimization because of inefficient vector-to-scalar translation. We present a framework for SIMD instruction translation and offloading for mobile devices (SIMDOM) in cloud and edge environments. The SIMDOM framework reduces the execution overhead of migrated vectorized multimedia application by using vector-to-vector instruction mappings. The framework maps and translates ARM SIMD intrinsic instructions to x86 SIMD intrinsic instructions such that an application programmed for the mobile platform can be executed on the cloud server without any modification. The offload decision is based on inputs from the device energy, network, and application profilers. Experiments show that SIMDOM framework provides 84.78%, 3.41%, and 79.93% energy, time, and performance efficiency, respectively, compared with local offload-disabled execution. Compared with compiled code offloading, the SIMDOM framework provides 55.99%, 57.50%, and 96.23% energy, time, and performance efficiency, respectively.